2010
DOI: 10.1016/j.aop.2010.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Bosons, fermions and anyons in the plane, and supersymmetry

Abstract: Universal vector wave equations allowing for a unified description of anyons, and also of usual bosons and fermions in the plane are proposed. The existence of two essentially different types of anyons, based on unitary and also on non-unitary infinite-dimensional half-bounded representations of the (2+1)D Lorentz algebra is revealed. Those associated with non-unitary representations interpolate between bosons and fermions. The extended formulation of the theory includes the previously known Jackiw-Nair (JN) a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 93 publications
1
49
0
Order By: Relevance
“…Later, a group-theory approach based on wave-functions was developed in 1 [9][10][11][12]. Later, a group-theory approach based on wave-functions was developed in [9][10][11][12]; see [13] for a summary and extensions of these models.…”
Section: Anyons and Statistical Gauge Fieldsmentioning
confidence: 99%
See 2 more Smart Citations
“…Later, a group-theory approach based on wave-functions was developed in 1 [9][10][11][12]. Later, a group-theory approach based on wave-functions was developed in [9][10][11][12]; see [13] for a summary and extensions of these models.…”
Section: Anyons and Statistical Gauge Fieldsmentioning
confidence: 99%
“…For ν < −1, but non-critical, these representations are still of a discrete type, but non-unitary. In reference [13] it was shown that the latter were essential for the construction of anyon wave equations possessing standard boson/fermion limits.…”
Section: Jhep02(2014)052mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several supersymmetric systems, concerned mainly with anyons in 2 + 1 dimensions [1][2][3][4][5] as well as with the 3+1 dimensional Majorana-Dirac-Staunton theory [6], uniting fermionic and bosonic fields, have been described. Furthermore, bosonic symmetries of the Dirac equation have been found in the massless [7] as well as in the massive case [8].…”
Section: Introductionmentioning
confidence: 99%
“…Having two parameters available in a mathematical model for the quantum oscillator, opens the way to more flexibility in applications. For possible applications (of the deformed algebra and its representations) in quantum field theory, see the ideas presented in [13].…”
Section: Resultsmentioning
confidence: 99%